(untitled) (Annals of Medical Research, 2021)
Aim: This study assessed the determinants of quality of life among chronic kidney disease patients and the socio -demographic variables contributing to the quality of life of chronic kidney disease patient attending Renal Clinics of two Tertiary Hospitals in Ondo State.Material and Methods: Descriptive cross sectional research design was utilized. Total enumeration method was used to select 140 respondents for the study. Adapted World Health Organization quality of life - BREF Version questionnaire was used to collect data, data generated were processed and analyzed using the Statistical Package for Social Sciences (SPSS) version 20; both descriptive and inferential statistics were used. Results: Finding revealed that the mean age of the respondent was 47.81±1.69 years. More (57.1%) of the respondents were males. The mean quality of life score of the respondents was found to be (38. 51±13.45). Results further showed that highest quality of life were observed in the environmental domain (mean score 16.21±5.66) followed by physical health (mean score 9.08±3.98) and the lowest in the social relation domain (mean score 5.13±3.31). Result showed that only family type is a significant determinant contributing to quality of life of patients (p = 0.038). There is no significant relationship between the socio demographic variable of respondent’ (age p= 0.12, gender p= 0.627, marital status p=0.167, educational qualification p=0.131) and their quality of life.Conclusion: Quality of life was poor among the respondents. To enhance the quality of life in patients with CKD, Good family and social relationships are of great importance and are the source of positive feelings and self-esteem as they improve the quality of life of patients.